Blood pressure characteristics of subclinical hypothyroidism: an observation study combined with office blood pressure and 24-h ambulatory blood pressure. Issue 3 (15th March 2021) - Cai, Peng; Peng, Yan; Chen, YuXi; Wang, Yan; Wang, Xukai
Abstract : Objective: To investigate the characteristics of blood pressure in subclinical hypothyroidism by combining office blood pressure and 24-h ambulatory blood pressure. Methods: A total of 3078 adults voluntarily participants were enrolled in this study between December 2017 and November 2019. Among 1431 of them who did not fit exclusion criteria, 104 patients were with subclinical hypothyroidism (S-HYPO group), and 1327 were euthyroid participants (euthyroid group). Office blood pressure measurement and 24-h ambulatory blood pressure monitoring were carried out to analyze the characteristics of blood pressure in subclinical hypothyroidism. Results: There was no statistical difference in office SBP and DBP between the S-HYPO group and the euthyroid group ( P >  0.05). On the ambulatory blood pressure level, the daytime SBP, night-time SBP, night-time SBP, 24-h SBP and DBP in the S-HYPO group were significantly higher than those in the euthyroid group ( P  = 0.048, P  = 0.002, P  = 0.003, P  = 0. 014, P  = 0. 046, respectively), and the proportion of nondipper blood pressure in the S-HYPO group was higher than that in the euthyroid group. Comprehensive analysis of blood pressure inside and outside the joint clinic revealed that the S-HYPO group was independently related to sustained hypertension and masked hypertension but not to white-coat hypertension ( P  = 0.004, P  = 0.002, P  = 0.886, respectively). After adjusting for age, sex, BMI, and other confounding factors, the above differences were still statistically significant ( P <  0.05). Conclusion: The characteristics of blood pressure in subclinical hypothyroidism can be more accurately understood by combining office blood pressure and ambulatory blood pressure.